STRATEGIC IMPLEMENTATION OF GLOBAL MARKETING MANAGEMENT: A CRITICAL EXPLORATION OF OPPORTUNITIES AND CHALLENGES IN A BORDERLESS ECONOMY - M. Villaronte, Christopher; Yuesti, Anik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
In an increasingly interconnected global economy, the effective implementation of Global Marketing Management (GMM) has emerged as a critical success factor for organizations across industries and scales. This study adopts a qualitative, exploratory approach to examine the strategic complexities of GMM, drawing from secondary data, scholarly literature, and real-world case studies. Focusing on Jollibee Foods Corporation—a Philippine-based multinational brand—the research explores how hybrid marketing strategies that integrate global standardization with local responsiveness are applied in practice. Key challenges identified include cultural misalignment, operational fragmentation, and legal and regulatory constraints, while enablers of success encompass cultural intelligence, integrated marketing communications, and real-time data analytics. The findings reveal that GMM is a dynamic and non-linear process requiring continuous adaptation to cultural, technological, and geopolitical shifts. This study offers strategic insights and practical implications for scholars, marketing professionals, and global business leaders seeking to navigate the evolving demands of international markets.